Bicornuate Bicollis Uterus with Obstruction of the Lower Uterine Segment and Cervical Prolapse Complicating Pregnancy - Kristen Stearns; Antoun Al Khabbaz (Hindawi Limited, 2018)
Congenital Mullerian duct anomalies are conditions involving the female genital tract. Cases of complex Mullerian duct anomalies with involvement of the renal system are rare. Occasionally, these cases can be associated with obstetrical complications. Cervical prolapse infrequently complicates pregnancy, and an association between uterine malformations and cervical prolapse has not been cited in the literature. We describe the case of a primigravid patient at 38 weeks of gestation noted to have cervical prolapse during evaluation for preeclampsia and labor induction. Obstetrical ultrasound at presentation to the labor and delivery suite revealed a high suspicion for a bicornuate uterus. The patient was delivered by cesarean section due to obstruction of the lower uterine segment of the gravid uterus. Further evaluation post-partum revealed a bicornuate bicolis uterus and renal agenesis. Pregnancies in patients with bicornuate bicollis uterus can be complicated by obstruction of the gravid uterus, resulting in cervical prolapse and necessitating cesarean section.